Effect of Combined Misalignments between the Shafts on the Contact Stress Distribution of Plastic Gears - S Phani Kuamr, KNS Suman, S. Ramanjaneyulu (International Journal of Advanced Science and Technology, 2020)
In the current endeavour, to study the contact stresses are observed in the plastic spur gears under different misalignment conditions. Plastic gears are utilized in the healthcare industry for quite a long time, it has been in the ongoing past the designers have begun to explore the benefits of using special compounds in medical applications. Contact stresses are powerfully reliant on the gear types, surface friction at the point of tooth contact, speed of the gear, centrifugal forces, etc. Contact stresses are also additionally relying upon the accurateness of bearing deflections, shaft bending deflection, housing thermal expansion, and shaft torsional deflections. The contact stress investigation is conducted with the help of FEM software ANSYS 15. The proposed method explains the deviation of contact stresses with the combined effect of varying inclination of the shaft axis, varying centre to centre distance between the shafts and radial misalignment of the gears. The inclination of the gear shaft axis, centre distance between the shafts, and radial distance between the gear faces can fluctuate due to wear of the bearings or any other causes of external effects. The stresses illustrate an increasing pattern with an increase of the combined effect of inclination of the shaft axis and distance between the shafts and minimum values are identified when the two shafts are parallel and maintained required distance.